Sex matters: repetitive mild traumatic brain injury in adolescent rats. Issue 9 (26th July 2017) - Wright, David K.; O'Brien, Terence J.; Shultz, Sandy R.; Mychasiuk, Richelle
Abstract: Objective: Whether sex differences contribute to the heterogeneity of mild traumatic brain injury (mTBI) and repeated mTBI (RmTBI) outcomes in adolescents is unknown. Therefore, this study examined changes in, and differences between, male and female rats following single mTBI and RmTBI. Methods: Rats were given a single mTBI, RmTBI (i.e., 3 x ), or sham injuries. Injuries were administered using a lateral impact model that mimics forces common in human mTBI. After the final injury, rats underwent extensive behavioral testing to examine cognition, motor function, and anxiety‐ and depressive‐like behavior. Postmortem analyses investigated gene expression and structural changes in the brain. Results: Many of the outcomes exhibited a sex‐dependent response to RmTBI. While all rats given RmTBI had deficits in balance, motor coordination, locomotion, and anxiety‐like behavior, only male rats given RmTBI had short‐term working memory deficits, whereas only females given RmTBI had increased depressive‐like behavior. Volumetric and diffusion weighted MRI analyses found that while RmTBI‐induced atrophy of the prefrontal cortex was greater in female rats, only the male rats exhibited worse white matter integrity in the corpus callosum following RmTBI. Sex‐dependent changes in brain expression of mRNA for glial fibrillary acidic protein, myelin basic protein, and tau protein were also observed following injury. Interpretation: These findings suggest that in adolescent mTBI, sex matters; and future studies incorporating both male and females are warranted to provide a greater understanding of injury prognosis and better inform clinical practice.